Cooperativismo, crédito e economia solidária na Central Única dos Trabalhadores (1983-2006) - Nadotti, Vanessa Xavier [UNIFESP] (2019)
The purpose of this work is to study the role of credit and cooperatives in the structuring of the Central Única dos Trabalhadores (Unified Workers' Central) during the period from 1983 to 2006. Cooperatives and credit are ideal within the CUT linked to the concept of Solidarity Economy. The research identified that from 1983 to the mid-1990s the trade union agenda focused on defensive and claiming strategies with strikes and deadlocks at the heart of the political struggle. We begin to elaborate and press for credit policies and cooperatives when we see in these the ideal alternative to unemployment and the growth of informality in the world of work. At that moment, with the exhaustion of the strike strategy, the CUT begins to formulate propositional policies. The creation of the Solidarity Development Agency (ADS) is the result of this new orientation of the trade union agenda. It represents a milestone in the course of the new union elaborations that sought at one and the same time to preserve one's own existence in a framework of unemployment and a growing sector of informality, and also to appease the ills provoked by this scenario, proposing a new model of development based essentially on the coming conceptualization solidarity economy. Under the principles of self-management, solidarity and democracy, they developed within the ADS a program to train workers and initiate them in the practice of cooperativism and struggle for credit. Our hypothesis is that this training process also served to link the cooperative to the union in a way that would guarantee its continuity and importance as one of the largest trade union centrals in the country. Since 2002, in the first year of the management of the Workers' Party, a specific government sector for the Solidarity Economy has been officially established, which reconfigures the financing policies of joint ventures. In this new political framework, the CUT sees its proposals reach the level of public policies, endorsing once and for all the tactic of encouraging a national network of credit cooperatives. Increasing the number of cooperatives would increase, therefore, the power of contribution and of its union base. It is a central hypothesis that the clashes, consensus and speeches formulated in this process produced a set of practices that pointed to the expansion of credit as a promoter of citizenship. While the expansion of the cooperative made possible by this, it has the capacity to signify both citizenship and interests that serve the business and employers sector that is free of employment links.